Upaya Meningkatkan Kreativitas Melalui Kegiatan Menggambar Dengan Media Audio Visual Pada Anak Kelompok B TK Dharma Wanita Kaliwiro Wonosobo Tahun Ajaran 2014/2015 - Ayu Saputri, Agustina; , Drs. Ilham Sunaryo, M.Pd AUD; , Junita Dwi Wardhani, SE. M,Ed (2015)
Drawing with audio visual media merupakan metode is an interesting and fun method for early childhood which will develop their creativity. Reality is happening in the learning activities in kindergarten many teachers are still using methods that are tedious to develop childern's creativity. The study aims to improve the creativity of children through drawing with audio visual media. The subject were student in group B kindergarten Dharma Wanita Kaliwiro Wonosobo in the academic year 2014/2015. This type of research is a classroom action research Jenis (PTK) with working procedures 2 (two) the cycle consists of four stages,Namely planning,implementation of the action, observation and reflection. These result indicate an increase in the creativity of the students. Research shows that the average child's creativity before action is 51,80%. After learning by doing activities drawing the audio visual in the first cycle of creativity of childern increased to62,73% in cycle two children creativity increased to 83,05%. Overall drawing with audio visual media can enhance the creativity of children in group B kindergarten Dharma Wanita Kaliwiro Wonosobo